Quantum chaos in optical microcavities: A broadband application(a)Contribution to the Focus Issue The Physics of Quantum Engineering and Quantum Technologies edited by Roberta Citro, J. Gonzalo Muga and Bart A. van Tiggelen. (16th October 2018) - Ge, Li
Abstract: Utilizing quantum chaos, a broadband and efficient coupling scheme has been demonstrated between a fibre and an optical microcavity. This approach may push optical microcavities with chaotic ray dynamics to fulfill their long-anticipated commercial potential.